ANALISIS RUGI- RUGI DAYA PADA PENGHANTAR SALURAN TRANSMISI TEGANGAN TINGGI 150 KV DARI GARDU INDUK KOTO PANJANG KE GARDU INDUK GARUDA SAKTI PEKANBARU - Muhammad Radil; Riad Syech; Sugianto s (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted on analysis of power losses on electric power transmission line of 150 kV of Koto Panjang to Garuda Sakti Pekanbaru in March 2014. This research was conducted and its aim was to analyze the power losses in the transmission system 150 kV. Conductors used in the high-voltage transmission line wasACSR (Aluminium Conductor Steel Reinforced) which consisted of a mixture of aluminum and steel with a diameter of 28.71 mm. Results of the transmission lineshowed that the largest total conductivity obtained was 43,645,705.993 Watt at 13:00 PM while the lowest total conductivity was 37,313,100.282 Watt at 17:00 PM. Highermagnitude of the transmitted conductivity resulted in increased power loss with ACSRconductor resistance of 0.049 Ω so that the largest loss occurred at 13:00 PM with4435.645 Watt power loss and the lowest power loss was 3,221.784 Watt at 17:00 PM.Based on the results obtained above, the percentages of power lost every hour for amonth in March 2014, were between 0.0086% to 0.0102% with the percentage ofoverall average power loss was 0.095%.